A plea for music - Keen, Letta Birdilla (My University, 1902)
Introduction: “As the guardian angel is said to follow us through life, so music seems to be ever with us in our journey from the cradle to the grave.” She sings beside our cradle, she kneels before the door of our tomb. In religion and in war she is ever present. At the dance and at the banquet, at every solemnity and at every feast. The songs of childhood, the songs which our mothers sang; who can be forgetful of their charm. The very youngest child is lulled and cheered by song before it knows the meaning of spoken words. When loves gentle impulse for the first time takes possession of the heart, the maiden gives expression to them in song, while the youthful lover delights in a serenade. It is hard to decide which is the mightier music or love. When listening with a believing mind and a feeling heart to the soft melody of the organ, the strains of the choir and the mighty song of the congregation, our souls are lifted upward on the wings of song until in the imagination we are in the blessed realms above. Music appeals to the better class of feelings as does nothing else. It has little or no power to arouse the uglier emotions. There is nothing stronger than music to make the sad joyful, the joyful sad, and the timid bold, to charm the haughty to humility, to calm and quiet excessive love, to lessen envy, and hatred. Tears have been started, hearts softened, sorrows stilled, religion deepened, aspiration awakened by music, but there never was and never can be written a strain of music which would excite the passion of greed, avarice, gluttony, angry or envy in the listener. It is through music that we communicate, or best of all commune with nature, for nature is the best musician, and he who has eyes to see but no lass to her beauties is in danger of never really knowing her. Music has been called “The Language of Heavens.” It might, perhaps better be said, music is the language of nature.
Citation: Keen, Letta Birdilla. A plea for music. Senior thesis, Kansas State Agricultural College, 1902.
Morse Department of Special Collections
Keywords: Music; Emotions; Theses